Salmonella regulation of intestinal stem cells through the Wnt/β-catenin pathway - Liu, Xingyin (2010)
Recent studies have revealed that bacteria target stem cells for long-term survival in a Drosophila model. However, in mammalian models, little is known about bacterial infection and intestinal stem cells. Our study aims at understanding bacterial regulation of the intestinal stem cell in a Salmonella colitis mouse model. We found that Salmonella activates the Wnt/β-catenin signaling pathway that is known to regulate stem cells. We identified Salmonella protein AvrA that modulates Wnt signaling including upregulating Wnt expression, modifying β-catenin, increasing total β-catenin expression, and activating Wnt/β-catenin transcriptional activity in the intestinal epithelial cells. The numbers of stem cells and proliferative cells increased in the intestine infected with Salmonella expressing AvrA. Our study provides insights into bacterial infection and stem cell maintenance.